2021
DOI: 10.1111/jdv.17336
|View full text |Cite
|
Sign up to set email alerts
|

Plantar involvement correlates with obesity, pain and impaired mobility in epidermolysis bullosa simplex: a retrospective cohort study

Abstract: Background Epidermolysis bullosa simplex (EBS) is the most common type of EB, a group of rare genodermatoses.Affected individuals suffer from skin blistering and report a high disease burden. In some EBS subtypes, plantar keratoderma (PK) has been described. Objectives This study investigated the presence and correlation of PK with body mass index, pain and mobility in EBS.Methods Individuals (n = 157) with genetically characterized EBS were included in this retrospective cohort study, and clinical data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Physical activity during childhood is primarily limited by pain from blisters on the feet. Over time, however, repeated cycles of wounding and healing can result in the development of plantar keratoderma, producing a cycle of increased pain followed by reduced physical activity and increased body weight as patients grow older [ 11 ]. Seasonal variation in mobility due to fluctuations in blistering and pain have also been identified, with symptoms often flaring in the summer due to increased heat and humidity [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical activity during childhood is primarily limited by pain from blisters on the feet. Over time, however, repeated cycles of wounding and healing can result in the development of plantar keratoderma, producing a cycle of increased pain followed by reduced physical activity and increased body weight as patients grow older [ 11 ]. Seasonal variation in mobility due to fluctuations in blistering and pain have also been identified, with symptoms often flaring in the summer due to increased heat and humidity [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One previous study also found that pediatric patients may encounter skepticism and a lack of empathy from peers who do not understand the fluctuating nature of EBS [ 32 ]. These difficulties may persist into adulthood, particularly among individuals unable to fully participate in work or social activities, and can contribute to worsening physical manifestations of disease including obesity due to social isolation and depression [ 11 , 14 , 29 ]. In the present study, 15% and 13% of adolescent and adult respondents used psychiatric medications, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They require multidisciplinary care, often suffer from extracutaneous manifestations, and later experience high psychological and socioeconomic disease burden 3,4 . Mild skin fragility leading to localized blistering on hands and feet may start later in life, but can likewise cause limitations in every‐day and professional activities, and reduction of the quality of life 5 . This latter group of EB patients likely remains underreported, either because it is not diagnosed, diagnosed later in life, or because it requires little or no medical care at all.…”
Section: Introductionmentioning
confidence: 99%